Protecting U.S. fisheries: strengthening the Magnuson-Stevens Act in a post-Chevron Deference era - Nicol, London, author; Olofsson, Kristin, advisor; Houghteling, Sam, committee member (Colorado State University. Libraries, 2025)
Overfishing and fishery collapse pose escalating environmental, economic, and social risks to the long-term stability of U.S. marine ecosystems. The Magnuson–Stevens Fishery Conservation and Management Act (MSA) has been the United States’ primary and most effective tool for preventing overfishing and rebuilding depleted fish stocks for nearly five decades. However, the Supreme Court's 2024 decision overturning Chevron Deference has introduced new legal uncertainty into the regulatory framework underpinning the MSA, exposing key conservation measures—particularly industry-funded monitoring requirements—to heightened litigation and judicial reinterpretation. This policy brief examines the implications of a post-Chevron regulatory landscape for U.S. fisheries governance, with a focus on monitoring provisions critical to detecting Illegal, Unreported, and Unregulated (IUU) fishing and ensuring compliance with catch limits and bycatch reduction standards. The analysis finds that while monitoring requirements remain essential to sustaining fishery health, mandating that fishers bear monitoring costs has generated persistent stakeholder opposition and legal vulnerability that threaten the durability of MSA protections. To preserve the effectiveness of U.S. fisheries management, this brief recommends that Congress strengthen the MSA by enacting explicit statutory authority for monitoring programs and shifting monitoring costs from industry to federal funding. Such reforms would reduce economic burdens on fishers, limit future litigation, reinforce regulatory stability, and safeguard the ecological and economic gains achieved under the MSA in a post-Chevron policymaking era.
College of Liberal Arts, Department of Political Science, Colorado State University.
Keywords: Magnuson–Stevens Act (MSA); U.S. fisheries management; overfishing; illegal, unreported, and unregulated (IUU) fishing; fisheries monitoring; Chevron Deference; Loper Bright Enterprises v. Raimondo; bycatch reduction; fishery collapse prevention; regulatory reform